Angular effects in the energy loss of slow protons and helium ions transmitted through thin Al and Au films - Archubi, Claudio Darío (2006)
Measurements of the energy loss of 10 keV protons and helium ions in Al and Au as a function of the exit angle are presented, as well as model calculations and numerical simulations taking into account the polycrystalline nature of the target. The experimental results show significant differences in the angular dependence between hydrogen and helium ions. To analyze this phenomenon we have studied the angular behavior of the energy loss by two different approaches. The first one is based on a theoretical method described in previous works. The second is based on a simulation code which takes into account the interaction of the projectiles with all the nearest neighboring atoms simultaneously, and incorporates the real polycrystalline characteristics of the target as obtained by transmission electron microscopy. The results indicate that a the different angular behavior of helium ions is mainly due to an impact parameter dependence of the energy loss for these ions; and b additionally we find that the influence of the crystalline structure on the angular effects of the energy loss is small for protons and somewhat more significant for helium ions.